Line Balancing with Simulation Approach (ProModel) on SMC Big Volume Lane in HA Export Department at PT. XYZ - Purwito, Dewanto Djoko; Ramlan Yuniar Velani; Diki Muchtar; Handayani , Suci Tresna Dewi (Sekolah Tinggi Teknologi Wastukancana, 2025)
This research aims to identify and overcome bottlenecks in production process at PT. XYZ Indonesia, especially in HA Export Department on SMC Big Volume Lane. Bottlenecks were detected in Visual Acc and Housing processes, which resulted in decreased efficiency and productivity. The method used in this study is line balancing with the Pro Model simulation approach, which allows analysis of improvement scenarios without disrupting ongoing operations. Data collected includes process time and machine capacity. Initial simulation results showed significant idle time 15,4%, with accumulation at Raw Material workstation (12.30%), Housing workstation (1.20%), and Visual Acc (1.90%). After the improvements were made, including increasing the Raw Material capacity to 20 pcs, the Housing process to 3 pcs, and Visual Acc to 3 pcs, the bottleneck was successfully eliminated from 15.4% became 0% and the production flow became more stable. This research provides practical solutions to improve efficiency and reduce cycle time, and can be a reference for companies in implementing line balancing and simulation methods to improve productivity in the manufacturing industry.